THE USE OF SIMULATION ENVIRONMENT FOR SOLVING THE ASSEMBLY LINE BALANCING PROBLEM - DANILCZUK, Wojciech (Applied Computer Science, 2018)
The paper describes the application of a simulation environment (Tecnomatix Plant Simulation) for solving a real manufacturing problem. The studied case consisted in rebalancing the production line with a specified number of operators on the line. The first stage of the study involved determination of the production cycle and key performance indicators. The production system was then divided into work cells. After that, proposed design assumptions were verified via a simulation model.